An Analysis of Darwin’s Theory of Natural Selection from Leibniz’s Perspective - Granados Zúñiga, Jorge (2025)
Charles Darwin published seven editions of The Origin of Species during his lifetime.  Starting from the premise that said book is philosophical, Chapter IV of the work was analyzed here to find the elements underlying the explanation of natural selection throughout the seven editions. Using the criteria established by Leibniz in his Dissertation on the Philosophical Style of Nizolio, it was determined that the philosophical quality in the first edition is intermediate and increased in the following editions, mainly in the third compared to the second.